Overview of DISCOVER22 experiment in the framework of INFN-LNGS Cosmic Silence activity: challenges and improvements in underground radiobiology - Morciano, Patrizia; Dini, Valentina; Berardinelli, Francesco; Baiocco, Giorgio; Conte, Valeria; Udroiu, Ion; Barbato, Federica; Marinaccio, Jessica; Anello, Pasqualino; Antoccia, Antonio; Tabocchini, Maria Antonella; Selva, Anna; et al. (Frontiers in Physics, 2023)
One of the most intriguing and still pending questions in radiobiology is to understand whether and how natural environmental background radiation has shaped Life over millions of years of evolution on Earth. Deep Underground Laboratories (DULs) represent the ideal below-background exposure facilities where to address such a question. Among the few worldwide DULs, INFN-Laboratorio Nazionale del Gran Sasso (LNGS) is one of the largest in terms of size and infrastructure. Designed and built to host neutrino and dark matter experiments, since the 1990s the LNGS has been one of the first DULs to systematically host radiobiology experiments. Here we present the DISCOVER22 (DNA Damage and Immune System COoperation in VEry low Radiation environment 2022) experiment recently started at LNGS. DISCOVER22 aims at investigating how the low radiation background modulates the Immune System (IS) response in in vitro and in vivo models. Underground radiobiology experiments are particularly complex and tricky to design and perform. In these studies, the accurate characterization of exposure scenarios is mandatory, but a challenging aspect is to understand how the very few ionizing tracks in the ultra-Low Radiation Environment (LRE) interact with the living matter in space and time in order to trigger different biological responses. In this Perspective, we describe these challenges and how we address them through a microdosimetric and a radiobiological approaches. We aim at linking physical microdosimetric measurements and the corresponding biological radiation responses by using radiation biophysical models that could shed light on many as yet unresolved questions.